Renin-angiotensin-aldosterone system and COVID-19 infection - Alexandre, Joachim (Ann Endocrinol (Paris), 2020)
With the multiplication of COVID-19 severe acute respiratory syndrome cases due to SARS-COV2, some concerns about angiotensin-converting enzyme 1 (ACE1) inhibitors (ACEi) and angiotensin II type 1 receptor blockers (ARB) have emerged. Since the ACE2 (angiotensin-converting enzyme 2) enzyme is the receptor that allows SARS COV2 entry into cells, the fear was that pre-existing treatment with ACEi or ARB might increase the risk of developing severe or fatal severe acute respiratory syndrome in case of COVID-19 infection. The present article discusses these concerns. ACE2 is a membrane-bound enzyme (carboxypeptidase) that contributes to the inactivation of angiotensin II and therefore physiologically counters angiotensin II effects. ACEis do not inhibit ACE2. Although ARBs have been shown to up-regulate ACE2 tissue expression in experimental animals, evidence was not always consistent in human studies. Moreover, to date there is no evidence that ACEi or ARB administration facilitates SARS-COV2 cell entry by increasing ACE2 tissue expression in either animal or human studies. Finally, some studies support the hypothesis that elevated ACE2 membrane expression and tissue activity by administration of ARB and/or infusion of soluble ACE2 could confer protective properties against inflammatory tissue damage in COVID-19 infection. In summary, based on the currently available evidence and as advocated by many medical societies, ACEi or ARB should not be discontinued because of concerns with COVID-19 infection, except when the hemodynamic situation is precarious and case-by-case adjustment is required.